Design and Prototype of an Automated Temperature Monitoring System for Kisoro Farmers’ Storage Facilities. - Nizeyimana, Denis (Kabale University, 2024)
Currently, the utilization rate of storage facilities for fruit and food crops in Kisoro is low, and it is necessary to carry out regional management of storage facilities to save energy and improve the utilization rate. Because different fruits and food crops need different temperatures, so real-time temperature monitoring is particularly important. To meet this requirement, this project designs an Arduino-based temperature monitoring system for Kisoro farmers’ storage facilities of fruits and food crops. The system mainly includes hardware and software parts. Hardware components include Arduino Uno, LM35 temperature sensor, SIM800A GSM, buzzer, LEDs (red and blue), and LCD, and the software component includes the Arduino IDE, Proteus. Finally, the whole system is tested, and the test results show that the system has the characteristics of remote viewing, high measuring accuracy, and convenient use, and the system could meet the needs of temperature management for Kisoro farmers’ storage facilities.